Safety and Efficacy of Laparoscopic Liver Resection for Colorectal Liver Metastasis With Obesity. Issue 6 (June 2021) - Inoue, Yoshihiro; Ishii, Masatsugu; Fujii, Kensuke; Nihei, Kentaro; Suzuki, Yusuke; Ota, Masato; Kitada, Kazuya; Kuramoto, Toru; Shima, Takafumi; Kodama, Hiroyuki; Matsuo, Kentaro; Miyaoka, Yuta; et al.
Introduction: Laparoscopic liver resection (LLR) in obese patients has been reported to be particularly challenging owing to technical difficulties and various comorbidities. Methods: The safety and efficacy outcomes in 314 patients who underwent laparoscopic or open nonanatomical liver resection for colorectal liver metastases (CRLM) were analyzed retrospectively with respect to the patients' body mass index (BMI) and visceral fat area (VFA). Results: Two hundred and four patients underwent LLR, and 110 patients underwent open liver resection (OLR). The rate of conversion from LLR to OLR was 4.4%, with no significant difference between the BMI and VFA groups ( P = .647 and .136, respectively). In addition, there were no significant differences in terms of operative time and estimated blood loss in LLR ( P = .226 and .368; .772 and .489, respectively). The incidence of Clavien-Dindo grade IIIa or higher complications was not significantly different between the BMI and VFA groups of LLR ( P = .877 and .726, respectively). In obese patients, the operative time and estimated blood loss were significantly shorter and lower, respectively, in LLR than in OLR ( P = .003 and < .001; < .001 and < .001, respectively). There was a significant difference in the incidence of postoperative complications, organ/space surgical site infections, and postoperative bile leakage between the LLR and OLR groups ( P = .017, < .001, and < .001, respectively). Conclusion: LLR for obese patients with CRLM can be performed safely using various surgical devices with no major difference in outcomes compared to those in nonobese patients. Moreover, LLR has better safety outcomes than OLR in obese patients.